Protective effect of isopsoralen on UVB‐induced injury in HaCaT cells via the ER and p38MAPK signaling pathways. Issue 8 (12th April 2022) - Yang, Liu; An, Lifeng; Wang, Yeqiu; Li, Jianmin
Abstract: This study investigated the protective effect of isopsoralen on UVB‐induced damage in HaCaT cells and its molecular mechanism. The cytotoxicity of isopsoralen and its effects on the viability of HaCaT cells were examined using the MTT assay. The effects of UVB irradiation and isopsoralen on the intracellular glutathione (GSH‐PX), superoxide dismutase (SOD), malondialdehyde (MDA), and reactive oxygen species (ROS) content were examined using commercially available assay kits. Further, the effects of UVB irradiation and isopsoralen on the levels of the inflammatory cytokines TNF‐α, IL‐6, and IL‐1α were examined using enzyme‐linked immunosorbent assay. Finally, we examined the effect of adding the estrogen receptor (ER) antagonist ICI182780, 780 and the p38MAPK antagonist SB203580 on the changes in inflammatory cytokines induced by isopsoralen treatment and UVB irradiation. Isopsoralen pretreatment markedly inhibited UVB‐induced reduction in the viability and proliferation of HaCaT cells. Isopsoralen also reduced UVB‐induced increase in the expression of the inflammatory cytokines and the level of free radicals (ROS and MDA), and reversed the UVB‐induced suppression of antioxidant activity. Additionally, inhibition of ER and p38MAPK via the addition of their respective antagonists reversed the observed anti‐inflammatory effects of Isopsoralen. Isopsoralen can efficiently provide protection against UVB‐induced damage in HaCaT cells brought about via oxidation and inflammatory reactions, and the underlying mechanisms involve the ER and p38MAPK pathways. Therefore, Isopsoralen could be used in therapeutic solutions for UVB‐induced skin conditions. Practical applications: Isopsoralen shows antioxidant and anti‐inflammatory effects. As natural, healthy, and effective additives, isopsoralen has been widely used in cosmetics and botanical medicine products. The results of this study reveal the molecular mechanisms underlying isopsoralen effects, showing that isopsoralen reverses the effects of UVB irradiation regulating ER and p38MAPK signaling pathways. Consequently, isopsoralen regulates the expression of ER and p38MAPK signaling pathways, thereby reducing the activation of antioxidant and anti‐inflammatory activity. These findings suggest that isopsoralen can be used as the base ingredient for antiphotoaging cosmetics and botanical medicine products. This study provides both theoretical and experimental background for isopsoralen deep processing and utilization.